A philosophical approach to entrepreneurship education: a model based on Kantian and Aristotelian thought. (18th December 2020) - Pellegrini, Massimiliano Matteo; Ciappei, Cristiano; Marzi, Giacomo; Dabić, Marina; Egri, Carolyn P.
In the field of entrepreneurship education, how to develop an effective program to teach entrepreneurship has been widely debated. However, an inductive approach based on analysis of educational program experiences and outcomes has led to mixed conclusions about the appropriate scope and structure of entrepreneurship education. In contrast, we take a deductive approach to develop a comprehensive entrepreneurship education model based on concepts from two schools of philosophical thought: the Kantian debate about freedom versus determinism, and the Aristotelian concepts of praxis and poïesis. These philosophical concepts are related to scope and structure dimensions that delineate the soft (art) and hard (science) of entrepreneurship education, their components and interrelationships. Pedagogies associated with each component as well as integrative pedagogies are identified to guide the development of entrepreneurship education programs and teaching. Theoretical propositions are presented for future research.